A prospective study of the bacteriological profile and risk factors of infection after internal fixation of close fractures of long bones - Borgohain, Munin; Bora, Debasish; Rajan, Aswin Deepak (International Journal of Research in Orthopaedics, 2020)
Background: Infection in implant related procedures is dreaded due to difficulty in getting rid of it. Disappointment to patients and surgeons, drainage of health care and patients’ resources is significant. Causes and risk factors are many related to host, environment and procedure. The bacteriological profile and antibiotic sensitivity have been changing trend with emerging resistance to many drugs. Methods: A prospective observational study of 941 patients with operative fixation of long bone closed fractures. The details of the procedure, host characteristics were noted. Followed up in ward post operatively and after discharge to identify the cases of surgical site infection. Once identified they were evaluated with X-rays and lab parameters. Wound swabs or pus samples taken to find out the organisms and cultured to find the sensitivity. Results: 116 patients (86 males and 30 females) developed SSI (incidence 12.42%). Plate fixation (18.20% infection rate), operative time >1 and half hours (15.73% rate), fracture femur (16.66% rate), ORIF (14.38% rate), age >60 yrs were some of the risk factors. Co-morbidities like anaemia, diabetes, liver disease, lung disease, immunosuppressive drugs, hypertension, smoking, alcoholics had significant association with SSI. Staphylococcus aureus was the most common organism. Gram positive showed highest sensitivity to linezolid, vancomycin and tetracycline. Gram negative showed highest sensitivity to colistin and tigecycline. Conclusions: Infection rate should be less than 1% and hence risk factors encompassing preoperative, intraoperative and postoperative period are to be controlled. Probably the first study from north east india showing the burden of orthopaedic SSI.